On the Meaning and Measurement of Suspects' Demeanor Toward the Police: A Comment on "Demeanor and Arrest" - Worden, Robert E. (Journal of research in crime and delinquency, 1996)
The article comments on a study published in the August 1996 issue of the "Journal of Research in Crime and Delinquency" on suspects' demeanor and its impact on police action. One of the most consistently replicated and widely accepted findings about police behavior is that police tend to sanction suspects who display a disrespectful demeanor toward the police. The proposition that police officers respond punitively to suspects who fail to accord them deference emerged from some of the earliest systematic inquiry into police behavior. Concern about the propriety of police action is raised especially by findings that police apply legal sanctions because citizens are disrespectful (or because they are African American or lower class), even in the absence of legal justification. Observers' characterizations of suspects' demeanor are only as valid as the instructions given to observers and the judgments that they make, and given how little we know about the forms of citizens' behavior that for officers represent affronts, one might be skeptical about the measures based on observers' characterizations